Cover Feature: Cooperative Adsorption of Metal‐organic Complexes on CsPbI2Br Perovskite Surface for Photovoltaic Efficiency Exceeding 17 % (ChemSusChem 23/2022). Issue 23 (18th November 2022) - Shi, Yiheng; He, Jingjing; Lian, Huijun; Liu, Xinyi; Yuan, Haiyang; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract : The Cover Feature shows a diethyldithiocarbamate molecule cooperating with a Zn cation to passivate the surface of a perovskite film. This strategy optimized the surface and realized power conversion efficiencies (PCEs) over 17 %. More information can be found in the Research Article by Y. Shi, J. He, H. Lian, et al .